Information and communication technologies for development in Africa. - Thioune, Ramata Molo.; International Development Research Centre Canada; Codesria ([Ottawa] [Dakar]: IDRC: CODESRIA, 2003)
Volume 1 looks at the introduction, adoption, and utilization of ICTs at the community level. In various contexts - geographical, technological, socioeconomic, cultural, and institutional - the book explores the questions of community participation. It looks at how communities in sub-Saharan Africa have reacted to the changes brought about by the introduction of these new ICTs and, in detail, presents both the opportunities and the challenges that ICTs present for community development. The book will be useful for both researchers and development practitioners active, or just embarking upon, an "ICT for development" program. It will also be a very useful reference tool not only for academics but also for policymakers, decision-makers, and development professionals interested in the issue.
Volume 2 examines the setting, operations and effects of community telecenters. It describes the telecenter experiences of a variety of local and often rural communities, exploring the management structures and mechanisms that have been established to support these telecenters. The book provides profiles of telecenter usage and discusses the potential and challenges of setting up and maintaining community telecenters in the context of poor information infrastructure and limited human capacity. It will be useful for researchers, policy- and decision-makers, and development practitioners and professionals with interests or active programs in the area of 'ICT for development, ' particularly those with a focus on universal access and universal-service or public access centers. It will also be a very useful reference tool for scholars, students and academics.
Volume 3 documents the processes used, and institutions created, to bring computers and connectivity into schools, as a means of enhancing the use and integration of ICTs in teaching and learning. A range of project, administrative, and cultural settings are explored as are a wide variety of technical solutions. The results, observations, and conclusions presented in this book will be useful for policy- and decision-makers in education and ICTs. The book will also be useful for teachers, researchers, and development practitioners and professionals with interests or active programs in the area of "ICT for development." Information technology professionals looking to service the potential education market will also find this book valuable.
v. 1. Opportunities and challenges for community development / edited by Ramata Molo Thioune -- v. 2. The experience with community telecenters / edited by Florence Ebam Etta and Sheila Parvyn-Wamahiu -- v. 3. Networking institutions of learning--Schoolnet / edited by Tina James.
Title from Web page (IDRC, viewed Mar. 28, 2006).
Published on the International Development Research Centre website.
Includes bibliographical references.
Keywords: Information technology -- -- Africa; Telecommunication -- -- Africa; Telecommuting centers -- -- Africa; Community development -- -- Africa; Technologie de l'information -- -- Afrique; Communication en développement communautaire -- -- Afrique; Développement communautaire -- -- Afrique; Electronic books -- Telecommunication; Electronic books